The Influence of Price, Registration Process, and Network Quality on Subscription Renewal Intentions with Perceived Ease as a Mediating Variable at IndiBiz Pangkalpinang - Deli, Deli; Suhardi, Suhardi (Jurnal Mantik, 2025)
This study aims to analyse the effect of service price, registration process, and network quality on IndiBiz customer satisfaction in Pangkalpinang, with customer trust as a mediating variable. IndiBiz services, which are intended for Micro, Small, and Medium Enterprises (MSMEs), face challenges in terms of price, administrative requirements, and network quality that influence customers' decisions to continue using these services. This study uses a quantitative approach with the Structural Equation Modelling (SEM) method to test the relationship between variables. The results show that service price and network quality significantly influence customer trust, while registration requirements have no significant direct influence on satisfaction. Customer trust proved to be a very strong mediating variable in bridging the influence of independent variables on customer satisfaction. These findings confirm that strategies to increase customer satisfaction should focus on building trust through the provision of quality services, fair prices, and ease of administration, in order to create loyalty and repeat subscription intentions among MSMEs.